Risky Business in China A Guide to Due Diligence - Gordon, J. (Palgrave Pocket Consultants, 2014)
Risk is a major reason that companies fail in, or fail to enter, China. Packed with case studies, this unique book demonstrates how correctly applied due diligence can not only reduce business risk in China, but also provide excellent business intelligence to support negotiations and business relationships.